SAR inspired by aldehyde oxidase (AO) metabolism: Discovery of novel, CNS penetrant tricyclic M4 PAMs. Issue 16 (15th August 2019) - Chopko, Trevor C.; Han, Changho; Gregro, Alison R.; Engers, Darren W.; Felts, Andrew S.; Poslusney, Mike S.; Bollinger, Katrina A.; Morrison, Ryan D.; Bubser, Michael; Lamsal, Atin; Luscombe, Vincent B.; Cho, Hyekyung P.; et al.
Graphical abstract: Abstract: This letter describes progress towards an M4 PAM preclinical candidate inspired by an unexpected aldehyde oxidase (AO) metabolite of a novel, CNS penetrant thieno[2, 3- c ]pyridine core to an equipotent, non-CNS penetrant thieno[2, 3- c ]pyrdin-7(6 H )-one core. Medicinal chemistry design efforts yielded two novel tricyclic cores that enhanced M4 PAM potency, regained CNS penetration, displayed favorable DMPK properties and afforded robust in vivo efficacy in reversing amphetamine-induced hyperlocomotion in rats.